"We Are Good Neighbors, But We Are Not Carers!": Lived Experiences of Conflicting (In)dependence Needs in Retirement Villages Across the United Kingdom and Australia. (3rd November 2021) - Carr, Sam; Fang, Chao
Abstract: Background and Objectives: This study sought to qualitatively explore the lived experiences of 80 older people living in retirement villages across the United Kingdom and Australia. We focused on residents' narratives around the themes of independence/dependence. Research Design and Methods: Qualitative semistructured interviews permitted in-depth exploration of how older people understood and experienced issues related to independence/dependence in the context of retirement living. Results: Core themes identified strikingly different and often competing needs and narratives around independence/dependence. Of note was the fact that narratives and needs around independence/dependence frequently collided and conflicted, creating a sense of "us" and "them" in the retirement community. The primary source of such conflict was reflected by the fact that residents seeking a "prolonged midlife" often felt that frailer and more dependent residents were a burden on them and were not suited to an "independent living community." Discussion and Implications: Our findings are discussed in relation to the challenges such competing narratives create for retirement villages as living environments for a group of people who are far from homogenous.